Evaluation of the energy value of plant species consumed by the Barbary Deer (Cervus elaphus barbarus, Bennet 1833) in the area of El Ayoune (El Kala National Park, Algeria) - Arbouche, Halima Saadia; Arbouche, Fodil (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 2007)
Plant species taken for food by the Barbary Deer were determined by direct observation during one year. On the basis of their chemical composition and phenological stage, the energy value of the grazed plant species has been expressed in stag-units as suggested by Brelurut et al. (1990). Results show that the more energy-giving elements are plants from the herbaceous layer and the acorns of Cork Oak (Quercus suber). From the shrubby layer, the Strawberry-tree (Arbustus unedo) comes first with an energy value comparable to that of green grass fodder, followed by Tree Heath (Erica arborea), Lentisc (Pistacia lentiscus) and Filaria (Phillyrea augustifolia) with energy values comparable to those of grass hays. The energy values of the other shrubby plant species are comparable with those of cereal straws; they do not ensure but the needs for maintenance.
Key W: AS
Keywords: grazed plant species; herbaceous; Quercus ilex.L; Quercus suber L.

Evaluation of the energy value of plant species consumed by the Barbary Deer (Cervus elaphus barbarus, Bennet 1833) in the area of El Ayoune (El Kala National Park, Algeria) - Arbouche, Halima Saadia; Arbouche, Fodil (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 2007)
Plant species taken for food by the Barbary Deer were determined by direct observation during one year. On the basis of their chemical composition and phenological stage, the energy value of the grazed plant species has been expressed in stag-units as suggested by Brelurut et al. (1990). Results show that the more energy-giving elements are plants from the herbaceous layer and the acorns of Cork Oak (Quercus suber). From the shrubby layer, the Strawberry-tree (Arbustus unedo) comes first with an energy value comparable to that of green grass fodder, followed by Tree Heath (Erica arborea), Lentisc (Pistacia lentiscus) and Filaria (Phillyrea augustifolia) with energy values comparable to those of grass hays. The energy values of the other shrubby plant species are comparable with those of cereal straws; they do not ensure but the needs for maintenance.
Key W: ASKey W: ASThe following values have no corresponding Zotero field: pub-location: 57 RUE CUVIER, 75005 PARIS 5, FRANCE publisher: SOC NATL PROTECTION NATURE ACCLIMATATION FRANCE
Keywords: grazed plant species; herbaceous; Quercus ilex.L; Quercus suber L.